1998
DOI: 10.1007/s003910050046
|View full text |Cite
|
Sign up to set email alerts
|

Psychometrische Demenzdiagnostik in der klinischen Praxis der Gerontopsychiatrie

Abstract: An extensive battery of cognitive tests is conducted to detect dementia in geriatric patients. Based on the ICD-10 diagnostic criteria for dementia the diagnosis includes cognitive deficits such as memory impairment and other cognitive disturbances in various stages. To establish a profile of cognitive deficits and to detect early stages of dementia a combination of psychometric tests has proven to be effective and valid (MMSE, SKT, SIDAM, GDS/BCRS, clock drawing). To evaluate interrelations between these test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…The SKT is known to be sensitive in early detection of cognitive de®cits (Ihl et al, 1992), but less sensitive in differentiating severe cognitive impairment (Gu Èrtler et al, 1998). Since the SKT is designed as a speed test, it may overestimate depressive features.…”
Section: Introductionmentioning
confidence: 99%
“…The SKT is known to be sensitive in early detection of cognitive de®cits (Ihl et al, 1992), but less sensitive in differentiating severe cognitive impairment (Gu Èrtler et al, 1998). Since the SKT is designed as a speed test, it may overestimate depressive features.…”
Section: Introductionmentioning
confidence: 99%
“…The early studies have verified the reliability of SKT of different cultures, which was similar to our research, the Cronbach's coefficient varies between 0.80 to 0.88. 18,19 . Erzigkeit's study 20 , based on a sample of 3789 subjects, showed that the reliability of memory and attention domain was very good.…”
Section: Discussionmentioning
confidence: 99%
“…Der Verlauf der Scores als Funktion der Klassenstufe deutet darauf hin, dass der Uhrentest bei normal entwickelten Kindern in einem Alter von etwa 10 Jahren keine diskriminierende Power in Bezug auf die Testleistung mehr hat. Dies entspricht dem "Ceiling effect", wie er auch beim MMSE bei leichten kognitiven Störungen beobachtet wird (8). Weitere Untersuchungen mit Testwiederholungen und Vergleichstests sind notwendig, um die Test-Retest-Reliabilität zu messen und die Validität einzuschätzen.…”
Section: Diskussionunclassified
“…In die Uhrentest-Aufgabe fließen sowohl visuokonstruktive und visuoperzeptive als auch mnestische Fähigkeiten ein. Der Uhrentest hat sich in der gerontopsychiatrischen Praxis als probates und für die älteren Patienten stressfreies Instrumentarium bewährt, um die kognitive Leistungsfähigkeit innerhalb weniger Minuten einzuschätzen und zu doku-mentieren (8). Zwischen den Uhrentest-Rängen und anderen Testverfahren (Syndrom-Kurztest, Mini-Mental-Status-Examination, Strukturiertes Interview zur Diagnose einer Demenz nach Zaudig) fanden Gürtler et al Beträge des Spearman-Korrelationskoeffizienten zwischen 0,56 und 0,62.…”
unclassified